The Handling of the Pandemic Covid 19 in the Consciousness of the Legal Community in Bali - Yogi Yasa Wedha; Holy One Singadimedja; Edy Nurcahyo; Ahmad Rosidi; Sara Ida Magdalena Awi (Publisher Cv. Inara, 2020)
This study discusses the legal awareness of the people of Bali are influenced by local wisdom in the face of pendemi covid-19. The purpose of this study is to analyze the success of handling Covid-19 in Bali in conjunction with legal awareness/ social culture of the Balinese people. There are two issues to be discussed, first how the legal regulation of countermeasures and efforts to break the chain of plague Covid-19 in Bali. Second, whether the local genius and social culture that has been there and is inherent in the fabric of Balinese life is effectively help the success of the handling of the Covid-19 in Bali ?The Research method used is normative law research Method reviewing the written law from various aspects, the approach of legislation (statute approach), the historical approach (historical approach), and a conceptual approach (conseptual approuach) and comparative approach (comparative approach) with the writing of descriptive analytical. The results of the research show that the Law is used to direct it to the goal-the desired destination, and creates patterns of behavior of new/social change in line with one of the functions of law, namely the function of the law as a means of social change, or a means to engineer society (social engineering). Tri Hita Karana (THK) as a frame of local wisdom in Bali in the life of indigenous peoples has been attached is the local wisdom that are rooted from culture and the hindu religion be a guideline and reference by the public in Bali to act/ behave this affects the legal awareness of the public to remain obedient and loyal in lawless in the community.